Muscle-specific deletion of Arid5b causes metabolic changes in skeletal muscle that affect adipose tissue and liver - Murray, Jennifer; Ehsani, Ali; Najjar, Liza; Zhang, Guoxiang; Itakura, Keiichi (Frontiers in Endocrinology, 2023)
Emerging evidence suggests that AT-Rich Interaction Domain 5b (Arid5b) may play a role in energy metabolism in various tissues. To study the metabolic function of Arid5b in skeletal muscle, we generated skeletal muscle-specific Arid5b knockout (Arid5b MKO) mice. We found that Arid5b MKO skeletal muscles preferentially utilized fatty acids for energy generation with a corresponding increase in FABP4 expression. Interestingly, in Arid5b MKO mice, the adipose tissue weight decreased significantly. One possible mechanism for the decrease in adipose tissue weight could be the increase in phospho-HSL and HSL expression in white adipose tissue. While glucose uptake increased in an insulin-independent manner in Arid5b MKO skeletal muscle, glucose oxidation was reduced in conjunction with downregulation of the mitochondrial pyruvate carrier (MPC). We found that glucose was diverted into the pentose phosphate pathway as well as converted into lactate through glycolysis for export to the bloodstream, fueling the Cori cycle. Our data show that muscle-specific deletion of Arid5b leads to changes in fuel utilization in skeletal muscle that influences metabolism in other tissues. These results suggest that Arid5b regulates systemic metabolism by modulating fuel selection.